PENGARUH EKSTRAK SAMBILOTO (AndrographispaniculataNees.) TERHADAP KUALITAS SPERMATOZOA EJAKULAT MENCIT (Musmusculus L.) SWISS WEBSTER - Zaima, Rahmapela; Sumarmin, Ramadhan; Widiana, Rina (Pendidikan Biologi, 2013)
ABSTRACT Sambiloto(Ind) or Bitter(Eng) Andrographis paniculata Nees., can used in the treatment of various diseases, such as influenza, cancer, antiinflammatory, antiHIV, antimitotic and antifertility.This study aimed to determine the effect of  the herbal bitter (Andrographis paniculata Nees.) to ejaculated sperm quality mice (Mus musculus L.). This research  was conducted  using Completely Randomized  Design  (CRD)  with  4 treatments and 6 replications, water and fed adlibitum. First treatment is given solvent extract. Second treatment extract were given 0.2 gram, third treatment were given 0,4 grams of extract and fourth treatment were treated exstrac 0,6 gram the orally for 36 days. After the mice decapitated, dissected and take sperm from vas deferens. Then, the sperm preparation determined using the improved Neubauer. Data were analyzed by ANOVA (Analysis of Varians).The results shoured at doses of 0,2 gram, the average sperm count was 12,00 x  decrease significant when compared with the control in which the average number of sperm 28,08 x  . So with this research the effective doses to decrease sperm count and can be used as a contraception medication dosage was 0,2 gram. It can be conclude that the extract of bitter (Andrographis paniculata Nees.) can decrease the quality of the ejaculated sperm of mice (Mus musculus L.)